Peningkatan kemampuan penalaran matematis siswa SMP: Study pengembangan media pembelajaran interaktif canva dengan model discovery learning - Rifdah Qultum Nada; Anik Yuliani; Tina Rosyana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
This investigation centers on the creation of interactive educational resources utilizing Canva, specifically those integrated with the Discovery Learning model. Furthermore, the study examines the media's validity, ease of use, and effectiveness in enhancing the mathematical reasoning capabilities of junior high school students. The chosen research methodology is R&D (Research and Development), which adheres to the ADDIE model. Data collection involved expert validation sheets, student response questionnaires, and mathematical reasoning ability assessment instruments in the form of pretests and posttests. The results verification indicated that the developed media achieved a "very good" standard and was suitable for use in teaching and learning environments. The implementation of this media demonstrated an increase in mathematical reasoning abilities among students in the experimental group, notably outperforming students in the control group. Based on statistical analysis, it can be concluded that the Canva-based interactive learning media, which incorporates the Discovery Learning model, has proven effective in improving the mathematical reasoning skills of junior high school students.